Factors Associated with Dyspepsia Among Patients at Tobelo Regional General Hospital - Olivia Asih Blandina; Devilya Pasimanyeku (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Dyspepsia is a non-communicable disease that not only occurs in Indonesia but also in other parts of the world. This study aims to identify factors associated with the incidence of dyspepsia in patients at the Tobelo Regional General Hospital. The sample size in this study was 90 respondents which was calculated based on the Slovin formula. This research uses quantitative research with descriptive analytical research methods and a cross-sectional approach, with the sampling technique accidental sampling. The research results showed that there was no relationship between dyspepsia and habits, types of food and drinks consumed, stress and gender. So there needs to be consistency in the delivery of information and education on good and ideal eating patterns to increase knowledge and prevent the occurrence of dyspepsia in the community.